PROPAGATION OF LONG-PERIOD DEFORMATIONAL DISTRIBANCES - Nevskiy M.V.; Morozova L.A.; Zhurba M.N. (My University, 1987)
The authors analyze the lateral time variation in longitudinal-wave velocities in the crust of a seismically active region. This required data from long-term seismic observations with controlled wave generators in dense areal seismic arrays. Reliable elucidation of the nature of the velocity variations requires laser measurements of strain on baselines comparable in length to the dimensions of the seismic array. Input data are the time series of differences between travel times of the first longitudinal waves, generated by shots of known position and time and recorded at epicentral distances of 25 to 150 km at 28 seismic stations in Southern California. This array of stations is isometric in shape and covers the main seismically active faults of the region, including the San Andreas Fault. For purposes of the analysis, the difference series are arranged in 28 × 25 matrices describing lateral and time variations in the observation period from 1975 to 1981. To determine the average intensity of the time variations of the differences and how the latter develop, the authors derived the structure function of the variations. Study results are discussed.